2015
DOI: 10.3892/etm.2015.2847
|View full text |Cite
|
Sign up to set email alerts
|

Fat-1 gene inhibits human oral squamous carcinoma cell proliferation through downregulation of β-catenin signaling pathways

Abstract: The ω-3 fatty acid desaturase (fat-1) gene encodes the enzyme that converts ω-6 polyunsaturated fatty acids (PUFAs) to ω-3 PUFAs. Numerous studies have suggested that the ratio of ω-6/ω-3 PUFAs has an impact on tumorigenesis. To investigate the biological function of the fat-1 gene in human oral squamous cell carcinoma (OSCC), the fat-1 gene was introduced into OSCC cells by transfection. The uptake of the gene was confirmed by reverse transcription-polymerase chain reaction and analyzed using gas chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The flamingo cadherin differs from the other cadherins—it has a transmembrane domain that spans the plasma membrane seven times, somewhat like that of G proteins, and participates in many cellular signaling pathways (33) (Figure 1). Fat and dachsous cadherins are very large cell-adhesion molecules (Table 1); a recent study showed the involvement of Fat cadherin in the Wnt-signaling pathway with the help of β-catenin (34) (Figure 1).…”
Section: Types Of Cadherinmentioning
confidence: 99%
“…The flamingo cadherin differs from the other cadherins—it has a transmembrane domain that spans the plasma membrane seven times, somewhat like that of G proteins, and participates in many cellular signaling pathways (33) (Figure 1). Fat and dachsous cadherins are very large cell-adhesion molecules (Table 1); a recent study showed the involvement of Fat cadherin in the Wnt-signaling pathway with the help of β-catenin (34) (Figure 1).…”
Section: Types Of Cadherinmentioning
confidence: 99%
“…Furthermore, PUFAs interfere with angiogenesis (VEGF, platelet derived growth factor-PDGF, MMP-2), cell cycle and proliferation (cyclins, p53, phosphate and tensin homolog-PTEN) molecules, all leading to the activation of tumorigenic pathways [79]. More specifically, ω-3 PUFAs have shown to contribute to the chemoprevention of oral cancer, by regulation via β-catenin signaling pathways [185] or via ERK1/2 phosphorylation [186]. In the end, one of the primary sources of lipid molecules is polyunsaturated fatty acids, representing the building blocks of the cell and its processes.…”
Section: Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 99%
“…On the other hand, FAT1 is involved in the structure and function of the glomerular cleft by podocytes and (Yu et al, 2017), it is important to note that FAT1 is also considered a tumor suppressor gene (Chen et al, 2019). An earlier study reported the loss heterozygosity of FAT1 may be an important factor in the development of astrocytic tumors (Nie et al, 2016).…”
Section: Fat1mentioning
confidence: 99%